Interactive Methods of Communication and Training to Deal with Adolescents and Youths with Deviant Behavior - Dushkina, M.R.; Chirkina, R.V. (Psihologiâ i pravo, 2019)
The article examines the problematique of increasing the effectiveness of specialists training in psychology and education of dealing with deviant behavior through the use of innovative interactive and interdisciplinary educational methods. Studying, discussing and analyzing the complex of current problems of socialization and personal development is delivered out with specific examples within the framework of the “Social Pedagogy” Course. It enables students to gain an in-depth understanding of the mechanisms, factors and determinants of deviant behavior, and contribute to the development of prevention and correction technologies. The key elements of the educational concept are scientific and practical orientation, increasing its relevance to the tasks of professional training by focusing on active methods of mastering the discipline and using modern technologies of social communications (simulation games, various types of discussions, TIPS-techniques, etc.). The result of this approach is the acquired skills and abilities, allowing them to design, organize and deliver appropriate work with children, adolescents and youth, including those with deviant behavior, in a modern society with a new technological context. В статье рассматривается проблематика повышения эффективности подготовки специалистов по педагогике и психологии девиантного поведения посредством применения инновационных интерактивных и междисциплинарных методов преподавания, ориентированных на актуальные социальные практики и феномены. Изучение, обсуждение и анализ комплекса современных проблем социализации и развития личности осуществляется на конкретных примерах в рамках курса «Социальная педагогика», что позволяет добиться углубленного понимания студентами механизмов, факторов и детерминант девиантного поведения, способствует разработке ими технологий превенции и коррекции. Особенностями концепции преподавания становятся научно-практическая ориентированность, повышение его релевантности задачам профессиональной подготовки специалистов посредством фокусировки внимания на активных методах освоения дисциплины и использования современных технологий социальных коммуникаций (имитационные игры, различные виды дискуссий, ТРИЗ-техники и др.). Результатом такого подхода является формирование у будущих специалистов компетенций, позволяющих им проектировать, организовывать и осуществлять соответствующую работу с детьми, подростками и молодежью, в том числе с девиантным поведением, в условиях современного общества с новым технологическим укладом.